Funding computer simulation of stem units in Vilnius University - Jegnoraitė, Rūta; Ivanauskas, Feliksas; Pikturna, Aleksas (Lietuvos matematikos rinkinys, 2010)
This paper aimed to develop a model which would optimize the distribution of state funding for university departments. Thus, computer-based simulation of Vilnius University budget was accomplished. The created model requires a special choice of weights – allocation for each unit’s optimal money demand approximation. This model can be used in every state university in order to optimize the distribution of state appropriations.